Expression and Characterization of Coprothermobacter proteolyticus Alkaline Serine Protease - Tanveer Majeed; Romana Tabassum; William J. Orts; Charles C. Lee (The Scientific World Journal)
A putative protease gene (aprE) from the thermophilic bacterium Coprothermobacter proteolyticus was cloned and expressed in Bacillus subtilis. The enzyme was determined to be a serine protease based on inhibition by PMSF. Biochemical characterization demonstrated that the enzyme had optimal activity under alkaline conditions (pH 8–10). In addition, the enzyme had an elevated optimum temperature (60°C). The protease was also stable in the presence of many surfactants and oxidant. Thus, the C. proteolyticus protease has potential applications in industries such as the detergent market.